The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/nu11081911
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Antioxidant Supplements and Uric Acid in Chronic Kidney Disease: A Review

Abstract: Increased serum levels of uric acid have been associated with the onset and development of chronic kidney disease (CKD), cardiovascular disease, and mortality, through several molecular pathogenetic mechanisms, such as inflammation and oxidative stress. Oxidative stress is present even in the early stages of CKD, progresses parallelly with the deterioration of kidney function, and is even more exacerbated in end-stage renal disease patients undergoing maintenance hemodialysis. Although acting in the plasma as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 123 publications
1
77
0
5
Order By: Relevance
“…In addition, the key urate-producing enzyme XDH was significantly increased in the HPD group compared with the CON group and was positively correlated with the serum urate levels. Hyperuricemia is closely associated with kidney excretion disorders [14,48]. We also detected MSU on the kidney surface, which indicates that inflammation occurred in the renal tissue.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, the key urate-producing enzyme XDH was significantly increased in the HPD group compared with the CON group and was positively correlated with the serum urate levels. Hyperuricemia is closely associated with kidney excretion disorders [14,48]. We also detected MSU on the kidney surface, which indicates that inflammation occurred in the renal tissue.…”
Section: Discussionmentioning
confidence: 58%
“…This is associated with several factors, such as malnutrition, dietary restrictions, or loss of vitamins and trace elements occurring during HD or PD (Liakopoulos et al, 2017Roumeliotis et al, 2019a). Implementing lifestyle interventions, such as administration of exogenous antioxidants, in patients with CKD on dialysis may downregulate the inflammation and oxidative stress associated with CVD-linked morbidity and mortality even in early stages of CKD (Liakopoulos et al, 2019a,b;Roumeliotis et al, 2019b). Indeed, several studies have investigated the possible benefits of exogenous antioxidant administration in both HD and PD patients.…”
Section: Changes In Cellular Balance Of Reactive Oxygen Species Can Cmentioning
confidence: 99%
“…CKD (Liakopoulos et al, 2019a,b;Roumeliotis et al, 2019b). However, further studies in large cohorts of HD and PD patients are necessary to determine the causality between antioxidant supplementation and clinical hard end-points of CVDs and allcause mortality.…”
Section: Changes In Cellular Balance Of Reactive Oxygen Species Can Cmentioning
confidence: 99%
“…It has been demonstrated that hyperuricemia is not only a risk factor for gout and chronic kidney disease, but also a risk factor for hypertension, hyperlipidemia, diabetes and cardiovascular disease, which are conditions that seriously affects human health (11)(12)(13)(14)(15)(16)(17). Therefore, xanthine oxidase inhibitors are commonly used in clinical practice to inhibit the synthesis of uric acid (18,19), but the effect is not as good as expected and has serious side effects (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%